ANALISIS FAKTOR PENGAMBILAN KEPUTUSAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI SMK BINA LATIH KARYA BANDAR LAMPUNG - Ajad Danijaya; Amiruddin; Riyuzen Praja Tuala; Yosep Aspat Alamsyah (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the factors influencing principals’ decision-making in improving teacher performance at SMK Bina Latih Karya Bandar Lampung. The research employs a qualitative approach with a case study design. Data were collected through in-depth interviews, observation, and documentation. The findings reveal that principals’ decision-making is influenced by personal factors, school culture, and the availability of information. These three factors contribute significantly to the improvement of teacher performance, particularly in terms of professionalism, discipline, and the quality of instruction. This study contributes to the development of educational management studies, especially in relation to contextual and participatory decision-making.